Tailored charge-neutral self-assembled L2Zn2 container for taming oxalate - Ocklenburg, David; Van Craen, David (Beilstein Journal of Organic Chemistry, 2024)
Dicarboxylic acids and their derivatives play crucial roles in various biological processes, necessitating the development of effective receptors for their detection. In particular, the smallest dicarboxylate, oxalate, presents a significant importance due to its widespread presence in nature and its association with various diseases. Yet, very little attention was devoted to the recognition of oxalate with metal-driven self-assemblies like cages or containers while numerous classic organic receptors for oxalate exist. This discrepancy is astonishing because metallocontainers or metallocages have advantages over classic macrocycles or organocages like a higher modularity and good preorganization paired with a ready receptor preparation by metal complexation. The reason for the underrepresentation is the competitive nature and excellent ligand properties of oxalate which not only is associated with the aforementioned diseases but also poses a serious hazard for metal-driven self-assemblies because the dianion can easily replace ligand strands leading to a partial or full receptor decomposition. Herein, we present a charge-neutral zinc(II)-based metallocontainer which was tuned to contest oxalate as most competitive dicarboxylate. The dianion is bound in a 1:1 fashion with a binding constant of log K = 4.39 selectively over other dicarboxylates by maintaining the receptor stability. This study highlights the importance of a highly modular receptor design so that tailored hosts can be designed to tackle the recognition of challenging competitive analytes.
Keywords: anion recognition; charge-neutral host; metallocontainer; oxalate